DINAMIKA PROSES KOMUNIKASI DAN TRANSFER INFORMASI KESEHATAN PADA PENGELOLAAN TAMAN TOGA - Yudhapramesti, Pandan; Srimulyani, Henny; Zulfan, Ipit (Interaksi: Jurnal Ilmu Komunikasi, 2019)
A community needs to be critical of various health information that is vulnerable to be misused. This article discusses the family medicinal plant development program (TOGA) managed by the PKK and the Women Farmers Group (KWT), in the cities of Semarang and Yogyakarta. In addition to teaching cultivation of family medicinal plants, this program is also an essential pillar of herbal health information literacy facilities for members of the organization. This qualitative descriptive study seeks to understand how the process of communication and transfer of information on herbal health takes place in the Herbal Bejo TOGA Park management program, contribute to the improvement of health literacy particularly in herbal health in a member of organizations. The results showed that trust and high compliance culture to instruc-tion and information of organization are helped members receive good quality and valid health messages because delivered by experts in their fields. On the other hand, changes in the socio-political climate compared to the New Order era and the devel-opment of technology have opened new experiences in organizational communication from the "top-down" vertical communication flow, changing into all directions, in-stantaneous and more democratic.